Innovative Model for Logo Counseling Website - Jacob Daan Engel; Ventje Jeremias Lewi Engel; Evangs Mailoa (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
Logo counseling is a counseling model specifically to treat low spiritual self-esteem problem affecting the life and attitudes of college students. Nevertheless, the problem relies on distance, time, and psychological burdens which preventing face-to-face logo counseling. By reviewing past research regarding online counseling practices, the innovative model for online logo counseling was designed and then demonstrated via logo counseling website. There are four objectives and thirty-five specifications defined in the model. The result showed that logo counseling website is helpful and easy to understand. Further research needed to address the issue of security and confidentiality, furthermore future research needed to examine the integration of text-mining and multimedia analysis techniques to better helping counselors in online counseling intervention.